Approximation of one class of differentiable functions by piecewise-HermitianL-splines - Novikov, S. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
The exact values of the upper bounds of deviations of piecewise-HermitianL-splines are found for certain classes of functions determined by systems of linear differential operators with continuous coefficients.